Answer:
Step-by-step explanation:
Ethan, this is a quadratic equation. We should rewrite this in standard quadratic form: 4x^2 + 16x - 9 = 0. Let's use the quadratic formula approach to solve this:
The coefficients of x are a = 4, b = 16 and c = -9. Thus, the discriminant is
b^2 - 4ac, or 16^2 - 4(4)(-9), or 256 - 144, or 112.
The two solutions are real and are as follows:
-16 ± √112 -16 ± √(16*7) -16 ± 4√7
x = ------------------- = ----------------------- = -----------------
2(4) 8 8
Or, after simplification,
-4 ± √7
x = --------------
2